B-type natriuretic peptide in athletes performing an Olympic triathlon - Banfi, G.; Migliorini, S.; Dolci, A.; Noseda, M.; Scapellato, L.; Franzini, C. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: Brain natriuretic peptide (BNP) is a cardioactive molecule produced in the myocardium. BNP is a sensitive marker of cardiac failure and its measurement in blood could be useful to the diagnosis and the treatment of this disease. Sporting activities, especially endurance ones, can induce cardiac problems, owing to the high workload for the myocardium during long and ultralong heavy effort. There are 2 papers describing the behavior of BNP in endurance events. BNP was elevated in marathoners, immediately after the race and also after 4 h. We studied the behavior of BNP in the triathlon, which is a complex sport characterized by 3 different activities (swimming, cycling, running). Methods: We recruited 49 athletes, all males, except for 4 females; 2 athletes did not finish the race and were not included in the statistical analysis in 2 different competitions. In these subjects we measured BNP using an immunological method before and after a triathlon. Results: No statistical significance between BNP values, before and after the triathlon, was found. Conclusion: We found no significant differences between pre- and postcompetition BNP values. Moreover, the range of values in both the blood drawings are similar of those of the general population, representing the biological variability of the analyte. The values in regularly trained athletes,, are not different from the general population and BNP is not modified by a triathlon, a typical endurance sport performance. We can underline that BNP increases in plasma are induced by heavy pathologies and are not influenced by physical activities, even strenuous ones.